An Evaluation of ‘Our Arabic Language’ Book for the Third Grade according to Visual Thinking Skills: Analytical Study - Alomoush, Reem AbdElkareem; Hamadneh, Munes Adeeb; Alissa, Rahmah Ahmad Salameh; Fraihat, Nesreen Bassam Fraid (International Journal of Membrane Science and Technology, 2023)
This study aims to identify the visual thinking skills needed for third-grade students in the primary stage and to evaluate Our Arabic language textbook according to these. To this end, a list of visual thinking skills was prepared and then converted into a tool for content analysis. The study sample consisted of all the pictures, drawings, and figures contained in the content of Our Arabic language book, amounting to (146) figures. Adopting the descriptive analytical approach, the results showed that Our Arabic Language book included visual thinking skills in general, but in a low percentage. The study recommends that emphasis be placed on including more visual thinking skills and finding a balance in the distribution of these skills.